Are environmental pollutants risk factors for low birth weight? - Luiz Fernando C. Nascimento; Douglas A. Moreira
The aim of this study was to assess the association between prenatal exposure to air pollutants and low birth weight in a medium-sized city. An ecological study was performed, using live birth data from São José dos Campos, São Paulo State, Brazil. The environmental data were obtained from the São Paul State Environmental Agency. The study included full-term newborns whose mothers were 20 to 34 years of age and had at least a complete high school education, seven or more prenatal visits, singleton pregnancy, and vaginal delivery, in order to minimize potential confounding from these variables. Logistic regression was used to estimate the effect of each pollutant. Low birth weight was defined as less than 2,500g. The sample included a total of 2,529 data from 2001 that met the inclusion criteria (25.6% of the total). We identified 99 newborns (3.95% of the sample) with low birth weight, and the pollutants sulfur dioxide and ozone were associated with low birth weight. The final model was À(x) = -1.79 + 1.30 (SO2) + 1.26 (O3). Thus, sulfur dioxide and ozone were identified as risk factors for low birth weight in a medium-sized city in Southeast Brazil.